Therapeutic education in chronic kidney hemodialysis patient - Fuentes Milián, Yangel (Revista Cubana de Nefrología, 2024)
Introduction: chronic kidney disease on hemodialysis requires an effort on the part of professionals to develop initiatives where they share educational scenarios with patients for health care, disease control and better therapeutic adherence. Objective: to analyze aspects related to therapeutic education in chronic renal hemodialysis patients. Methods: a documentary review was carried out on therapeutic education in chronic kidney hemodialysis patients, in national and foreign publications, using the PubMed, Scielo and Dialnet databases. All documents published in the last five years were selected, which included the key words: Therapeutic education, Chronic kidney disease, Hemodialysis. Results: the analysis carried out allows us to argue that therapeutic education of chronic kidney patients on hemodialysis requires promoting behaviors and lifestyles in self-care management; that respond to the patient’s needs in the context of her own reality. Conclusions: education provides a broad base of knowledge and skills to achieve behavioral changes, which are necessary to successfully adapt to the new situations generated by chronic kidney disease on hemodialysis. Keywords: Therapeutic education, Chronic kidney disease, Hemodialysis.